Optimalisasi Peran Teknologi Digital dalam Meningkatkan Penerimaan Zakat Infaq dan Shadaqah - Denas Hasman Nugraha (STAI Terpadu Yogyakarta, 2022)
In the process of this digital fundraising strategy activity, an institution or organization must always carry out socialization, education, and promotional activities that are packaged technologically. Where the purpose of implementing this strategy is to increase the collection of Zakat, Infaq, and Shadaqah funds. From the qualitative authorship method that the author uses, the discussion obtained related to the use of digital technology in increasing the acceptance of zakat, infaq and shadaqoh is quite varied. Such institutions actively utilize technology. Among the digital technologies that are quite popular and used in providing information, services and distribution include: website, instagram, tiktok, facebook, twitter and youtube. Almost all of these zakat, infaq and shodaqoh institutions have this account. And with the use of this media is quite effective in raising funds from muzakki and or donors.